Cobalt@Nitrogen‐Doped Porous Carbon Fiber Derived from the Electrospun Fiber of Bimetal–Organic Framework for Highly Active Oxygen Reduction. Issue 12 (2nd May 2018) - Bai, Qing; Shen, Feng‐Cui; Li, Shun‐Li; Liu, Jiang; Dong, Long‐Zhang; Wang, Zeng‐Mei; Lan, Ya‐Qian
Abstract: The exploitation of high‐efficiency, cost‐effective, and stable oxygen reduction reaction (ORR) electrocatalysts is extremely critical for energy storage and conversion technology. The transition metal carbonitrides have been investigated as an alternative to precious metal‐based catalysts. Here, a series of uniform Co nanoparticles encapsulated in nitrogen‐doped porous carbon fibers (Co@N‐PCFs for brevity) are designed and synthesized by directly carbonizing the Zn x Co1– x ‐zeolitic imidazolate frameworks@polyacrylonitrile (Zn x Co1– x ‐ZIFs@PAN) electrospun nanofibers. By precisely controlling the Zn/Co molar ratio in the Zn x Co1– x ‐ZIFs precursor and carbonization temperature, a higher activity and stability ORR catalyst of Co@N‐PCF‐3 is prepared. The results reveal that Co@N‐PCF‐3 exhibits outstanding ORR activity outperformed commercial Pt/C with more positive half‐wave potential of −134 mV versus Ag/AgCl, high selectivity to four‐electron pathway ( n ≈ 3.9), as well as remarkable stability and methanol tolerance. Remarkably, it is one of the highest ORR catalysts among the cobalt carbonitrides reported in the literature. Abstract : A series of uniform Co nanoparticles encapsulated in nitrogen‐doped porous carbon fibers (Co@N‐PCFs for brevity) are well designed and synthesized by directly carbonizing the Zn x Co1– x ‐zeolitic imidazolate frameworks@polyacrylonitrile (Zn x Co1– x ‐ZIFs@PAN) electrospun nanofibers. The results reveal that Co@N‐PCF‐3 exhibits outstanding oxygen reduction reaction (ORR) activity that outperformed commercial Pt/C with more positive half‐wave potential of −134 mV versus Ag/AgCl, high selectivity to four‐electron pathway, remarkable stability, and methanol tolerance.